2019
DOI: 10.3168/jds.2019-16433
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid efficiencies of utilization vary by different mechanisms in response to energy and protein supplies in dairy cows: Study at mammary-gland and whole-body levels

Abstract: Variations of mammary gland (MG) metabolism were studied in dairy cows in response to diets containing 2 levels of net energy of lactation [NE L ; 25.0 and 32.5 Mcal/d for low (LE) and high energy (HE), respectively], combined with 2 levels of metabolizable protein [MP, 1,266 and 2,254 g/d of protein digestible in the intestine for low (LP) and high protein (HP), respectively] in a 2 × 2 factorial arrangement. Four cows received 4 diets (LELP, HELP, LEHP, and HEHP) in a 4 × 4 Latin square design with 2-wk expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…However, few studies have reported the relationship between efficiency of mammary AA utilization and RFI. Many studies have been conducted to improve AA utilization efficiency through nutritional manipulation, such as infusing AA or hormones [ 20 , 21 ] and altering dietary levels of energy or protein [ 22 ]. In comparison with nutritional manipulation, genetic selection may provide cumulative, longer-term enhancements of traits [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported the relationship between efficiency of mammary AA utilization and RFI. Many studies have been conducted to improve AA utilization efficiency through nutritional manipulation, such as infusing AA or hormones [ 20 , 21 ] and altering dietary levels of energy or protein [ 22 ]. In comparison with nutritional manipulation, genetic selection may provide cumulative, longer-term enhancements of traits [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of energy and MP supplies on MPY have been reported to be additive and independent (Broderick, 2003;Raggio et al, 2006;Omphalius et al, 2019a), except in one study (Brun-Lafleur et al, 2010). Increased energy intake or postruminal glucose infusion led to an increased efficiency use of MP, whereas an increased MP supply decreased it (Omphalius et al, 2019a(Omphalius et al, , 2020. Maintaining an adequate supply of EAA with a reduced supply of MP combined with an increased energy supply might further increase MP efficiency use and MPY.…”
Section: Introductionmentioning
confidence: 93%
“…The functions of amino acids have been extensively studied in the gut, liver, muscle and adipose tissue, especially in the field of protein (4) and fat metabolism (5) . In the mammary gland, amino acid uptake from blood is almost equal to milk output based on a nitrogen basis in dairy cows (6)(7)(8) , goats (9) , sows (10) and ewes (11) . However, the destinies of different amino acids in mammary cells are different (6)(7)(8)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…In the mammary gland, amino acid uptake from blood is almost equal to milk output based on a nitrogen basis in dairy cows (6)(7)(8) , goats (9) , sows (10) and ewes (11) . However, the destinies of different amino acids in mammary cells are different (6)(7)(8)(10)(11)(12) . The mammary amino acid uptake:output ratios could be larger (for example, valine, isoleucine, leucine and arginine), equal (for example, methionine and histidine) or less than 1 (for example, asparagine and proline) (mammary amino acid uptake:output ratios in cows, goats, sows and ewes are shown in Table 1) (6)(7)(8)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation